PATHWAY OF INFECTION IN CANINE FOSSA SPACE ABSCESS - Cristiani Nadya Pramasari (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: Most of fascial space infections of head and neck caused by odontogenic infections. The canine space becomes involved primarily as the result of infections from the maxillary canine tooth. The buccal space may become infected from extensions of infection from either the maxillary or mandibular teeth.Purpose: This case report discusses the management of canine fossa space abscess extending to buccal space.Case: A-45-years-old male patient came to the A.W. Sjahranie Hospital with complaints of swelling in his left face since two weeks ago. Physical examination showed swelling in the upper left jaw. CT scan’s view showed a radiolucent appearance of the canine fossa region. Panoramic radiograph pointed upper left canine (23) and first molar (26) as source of infection. Based on clinical and radiographic examinations, the patient was diagnosed with a canine fossa space abscess. Case Management: The treatment was given are intravenous antibiotics, multiple tooth extraction followed by intraoral drainage incision under general anesthesia.Conclusion: Extension of infection of the canine fossa space can lead to the buccal space and maxillary sinus at the same time due to multiple carious tooth. Keywords : Buccal space abscess, Canine fossa space abscess, Maxillary sinus, Odontogenic infection